(3GdeNJGQ ef TYQ egjGQs - (3CHhGdbGSe Ydj Hf oefLH Hf SdjeGf GdcGJH, GdeYQha HGHf GdUjQaj GdeUQjs; (3egjGQ GdOjdej , egjGQ Hf eQRhjg GdOjdej, CHh GdMSf,J (B428 (3g` s
(3ChdgG (B:s
(3gPG LRA JNjQJg ef TYQ CHj GdMSf egjGQ Hf eQRhjg GdcGJH QJHJg CHhGHkG dCf Pdc CfaY ajeG jJNjQ ddeJeKd s
(3BNQgG (B:s
-(3heG Gdoqefj aj GdCYfGb EdG LhGeY (B-(3Ef GdSchJ Yf GdCLhGO JPcjQ Je GdLRA GdeNJGQ, hGdMeO ddg hMOg s
(3HGdeYgO fSNJGf ef OjhGf egjGQs
(3GfXQgeG aj GdLRA GdChd GdbSe GdChd HQbe (B361 (3COHs
(3hGdbSe GdKGdK HQbe (B1657 (3COH s
(3HChdgG HNW eNJda JQLeI degjGQ efbhdI ef (B"(3GdhGaj HGdhajGJ(B" (3dUdGM GdOjf GdUaOj s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B264s
Keywords: (3GdCOHs